Preparation of calcium carbonate binders via CO2 activation of magnesium slag. (July 2019) - Mo, Liwu; Hao, Yuanyuan; Liu, Yunpeng; Wang, Fazhou; Deng, Min
Abstract: Magnesium slag, an industrial byproduct containing high contents of CaO and MgO, was activated with CO2 to prepare calcium carbonate binders via accelerated carbonation. The mechanical strength, microstructure, and volume stability of the carbonate binders were investigated. Results show that calcium carbonate binders with high compressive strengths of up to 119.5 MPa are prepared via accelerated carbonation of magnesium slag pastes. This is attributed to the formation of calcium carbonates in terms of calcite and vaterite, yielding an enhanced product matrix with dense microstructure and high mechanical performance. The water to magnesium slag ratio (W/S) strongly influences the compressive strengths of the carbonate binders, and increasing W/S ratio decreases the compressive strengths. CO2 activated magnesium slag paste shows a stable volume without causing excessive expansion when cured in 60 °C water. This study provides a new way to prepare calcium carbonate binders integrating the magnesium slag recycling and CO2 sequestration.